Enhanced gas separation performance of PSF membrane after modification to PSF/PDMS composite membrane in CO2/CH4 separation - Suleman, M.S. (John Wiley and Sons Inc., 2018)
Asymmetric polysulfone (PSF) membrane was developed and modified to PSF/polydimethylsiloxane (PSF/PDMS) composite membrane by dip coating technique. Effect of PDMS coating time on membrane properties was examined by scanning electron microscopy, thermogravimetric analysis, differential scanning calorimetry, attenuated total reflectance-Fourier transform infrared, and water contact angle. The increase in PDMS coating time resulted in a decrement in the thermal strength of PSF membrane. Surface contact angle values revealed that increase in PDMS coating time had increased the surface hydrophobicity in membranes. CO2/CH4 separation performance of membranes was evaluated, and an increase in CO2/CH4 ideal selectivity was observed with the increase of PDMS coating time. At feed pressure of 10 bar, the selectivity of PSF has increased up to 65 after dip coating with PDMS for 30 min. Modification of polymeric membrane into composite membrane provided a way forward towards the enhancement of gas separation performance in polymeric membranes. Â© 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2018, 135, 45650. Â© 2017 Wiley Periodicals, Inc.